Effects of gaseous nitriding AISI4140 alloy steel on corrosion and hardness properties - Moli L.T.; Wahab N.; Gopinathan M.; Karmegam K.; Maniyarasi M. (Institute of Physics Publishing, 2023)
Aerospace engineering; Corrosion; Corrosion rate; Corrosion resistance; Failure (mechanical); Hardening; Hardness; Machinery; Nitriding; Nitrogen; Pitting; Safety engineering; Steel metallurgy; Surface treatment; Corrosion behaviour; Gaseous nitriding; Immersion testing; Maintenance cost; Mechanical failures; Root cause of failures; Surface hardening; Surface hardness; Alloy steel